Head and neck non-metastatic cancer associated hypercalcemia - Lazutkin, Anna; Eliashar, Ron; Weinberger, Jeffrey M.; Hirshoren, Nir (International Surgery Journal, 2019)
Cancer associated hypercalemia (CAH) is a relatively common paraneoplastic syndrome and may be associated with head and neck cancer patients. As the hypercalcemia may be life-threatening, recognition is paramount. Herein we investigate the prevalence and outcome metrics of CAH and create a proposed clinical guideline for advanced stage head and neck malignancies. We describe our experience with non-metastatic, asymptomatic persistent head and neck CAH, which resolved after surgical ablation. We have performed a literature search in the PubMed database between the years 1998-2018 using the key words "head neck", "squamous cell carcinoma", "hypercalcemia", "cancer associated hypercalcemia" and "paraneoplastic. Non-metastatic head and neck CAH generally presents in patients with advanced stage disease and is associated with poor prognosis (median survival time range 28-64 days). It may portend imminent distant spread. Most patients continue to suffer from persistent high calcium levels despite treatment. We present a patient with nodal recurrence of advanced stage IV oral cavity squamous cell carcinoma and CAH. Regional neck metastases were surgically excised, resulting in normalization of blood calcium levels. Hypercalcemia should be ruled out in all advanced head and neck cancers. Treating physicians should be aware and promptly treat severe hypercalcemia. CAH may herald advanced disease, thereby modifying treatment decisions. However, in cases where surgical ablation is feasible, it is the preferred management for achieving calcium normalization.